Potential role of report nudging on diagnosis and treatment of ventilator-associated pneumonia: a quantitative survey - Kimberly C. Claeys; Blaine Kenaa; Ravi K. Tripathi; Kristen Rayner; Michelle Newman; Surbhi Leekha (Antimicrobial Stewardship & Healthcare Epidemiology)
Diagnosis of ventilator-associated pneumonia (VAP) is challenging and relies heavily on respiratory culture results. The results of this survey underscore the potential for a diagnostic stewardship nudge limiting culture reports to “potential colonization or contamination” in those without clinical findings of VAP to decrease unnecessary antibiotic prescribing.